2020
DOI: 10.3390/jcm9082371
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Low-dose Atropine with Orthokeratology in Pediatric Myopia Control: Review of the Current Treatment Status for Myopia

Abstract: Pediatric myopia has become a major international public health concern. The prevalence of myopia has undergone a significant increase worldwide. The purpose of this review of the current literature was to evaluate the peer-reviewed scientific literature on the efficacy and safety of low-dose atropine treatment combined with overnight orthokeratology for myopia control. A search was conducted in Pubmed and Web of Science with the following search strategy: (atropine OR low-dose atropine OR 0.01% atropine) AND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 91 publications
0
26
0
1
Order By: Relevance
“…Studies have evaluated the ability of atropine in myopia control and its side effects at different concentrations [ 17 , 18 ]. Atropine, an anticholinergic that causes pupillary dilation, is contraindicated in glaucoma [ 31 , 32 , 33 , 34 ]. Because of a shallow anterior chamber in children, ophthalmologists have a concern regarding whether using atropine for treating children with myopia will affect their IOP due to the induction of mydriasis by muscarinic antagonists [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have evaluated the ability of atropine in myopia control and its side effects at different concentrations [ 17 , 18 ]. Atropine, an anticholinergic that causes pupillary dilation, is contraindicated in glaucoma [ 31 , 32 , 33 , 34 ]. Because of a shallow anterior chamber in children, ophthalmologists have a concern regarding whether using atropine for treating children with myopia will affect their IOP due to the induction of mydriasis by muscarinic antagonists [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the total duration (X8) is related to high IOP in children with myopia because total time-lapse exhibited the onset of myopia and atropine exposure. A longer total duration suggests that the patient had myopia onset at a younger age and was using atropine for an extended period [ 32 , 33 , 34 , 35 ]. The total duration of atropine usage should be considered when following IOP in children with myopia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as long as long-term stability and microbiological safety are considered, appropriately unpreserved ophtioles and vials can also be used. Facing the additive effect of atropine with orthokeratology, the use of preservative-free solutions might allow a more gentle treatment, sparing the integrity of and avoiding toxicity to the corneal epithelium [ 38 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the effect of combining low-dose atropine eye drops with orthokeratology in attempts to enhance efficacy. Recent meta-analyses of these studies [ 11 , 12 , 13 ] have concluded that this combination can significantly improve efficacy in slowing progression relative to the efficacy of orthokeratology alone.…”
Section: Introductionmentioning
confidence: 99%